PERSEPSI MASYARAKAT TERHADAP PEMBANGUNAN PEMBANGKIT LISTRIK TENAGA PANAS BUMI (PLTP) DI KECAMATAN PAUH DUO KABUPATEN SOLOK SELATAN - Taufik Iqbal (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
The background of this research is the development of a Geothermal Power Plant (PLTP) in the District of Pauh Duo, where renewable energy is needed as an alternative to replacing fossil energy which is dwindling. However, the development of this PLTP certainly has an impact on the community around the construction site, both the impacts that are felt socially, economically, and environmentally. Resulting in various perceptions among the people. This study aims to determine how people's perceptions of the development of the Geothermal Power Plant (PLTP) in the District of Pauh Duo, South Solok Regency. This research is a type of descriptive research that uses a quantitative approach. The population of this research is the community of Pauh duo sub-district. Researchers use cluster sampling techniques in determining the sample. The samples in this study were 99 people. Data collection techniques used in this study were questionnaires as primary data collection techniques, in the form of questionnaires to the public. As well as documentation as a secondary data collection technique. Then the data is processed using the SPSS application. Based on the results of the questionnaire that was distributed to the community, the results of the community's perception of the development of the Geothermal Power Plant (PLTP) were seen from the social aspect having a fairly good perception index with a percentage of 56.89 percent. Viewed from the economic aspect it has a fairly good perception index with a percentage of 60.35 percent. Viewed from the aspect of the environment it has a good perception index with a percentage of 76.29 percent.